Comparative arts studies as the main factor in the preparation of future music teachers for practical work in the new Ukrainian school - Bezemchuk, Bezemchuk; Fomin, Volodymyr (Professional Art Education, 2024)
The article explores the importance of implementing the content module “Comparative Art Studies as a Key to Teaching the Integrated Course “Art” in the New Ukrainian School. The role of comparative analysis in the context of training future music teachers is revealed. Methods and methodology. The article uses the method of scientific research and practical methods of studying the results of creative work of applicants for higher pedagogical education during the performance of educational tasks. Scientific novelty. For the first time, an attempt is made to include the content module “Comparative Art Studies – the Key to Teaching the Integrated Course “Art” in the New Ukrainian School” in the educational program of professional training of students of the specialty 014.13 Secondary Education (Musical Art). The topic of the module content and the methodology for conducting comparative analysis for work in integrated fine art lessons are revealed. The results of the study showed that students are aware of the existence of comparative art in the field of scientific knowledge and have a certain idea of the integrated principle of teaching in art lessons in secondary education institutions. The interest of students in conducting comparative analysis in the process of comparing different types of art during practical work was established. Creative works in the form of video lessons were demonstrated, where comparative art is the key to understanding the principle of integrated teaching of students. A certain interest in the development of modern trends in online learning, such as fractal graphics, was identified. Conclusions. Given the intensive development of the reforms of the New Ukrainian School, there is a need to actively involve music teachers in this process, who could master the methodology of involving students in integrated learning in the context of the ideas of comparative art. This requires specially organized training of future music teachers within the framework of the implementation of educational programs, the formation of comparative analysis skills in them as the main method of conducting art lessons. Prospects for further research can be considered issues related to the formation of integration and pedagogical skills of future music teachers for working with children in secondary schools.